Упростите выражения: а) (х+2)(2х-1) б) (2-у)(у²+3) в) (а+4)(1-а)+а² г) (b+2)(b²-b+2)
Упростите выражения:
а) (х+2)(2х-1)
б) (2-у)(у²+3)
в) (а+4)(1-а)+а²
г) (b+2)(b²-b+2)
Ответ(ы) на вопрос:
Гость
[latex](x+2)(2x-1)[/latex]
[latex]2x^2-x+4x-2[/latex]
[latex]2x^2+3x-2[/latex]
[latex](2-y)(y^2+3)[/latex]
[latex]2y^2+6-y^3-3y[/latex]
[latex](a+4)(1-a)+a^2[/latex]
[latex]a-a^2+4-4a+a^2[/latex]
[latex]a+4-4a[/latex]
[latex](b+2)(b^2-b+2)[/latex]
[latex]b^3-b^2+2b+2b^2-2b+4[/latex]
[latex]b^3+b^2+4[/latex]
Гость
а) (х+2)(2х-1)=2х²-х+4х-2=2х²+3х-2;
б) (2-у)(у²+3)=2у²+6-у³-3у;
в) (а+4)(1-а)+а²=а-а²+4-4а+а²=4-3а;
г) (b+2)(b²-b+2)=b³-b²+2b+2b²-2b+4=b³+b²+4
Не нашли ответ?
Похожие вопросы